El control interno del proceso de contratación de obras públicas y su relación con el presupuesto del gobierno autónomo descentralizado municipal del cantón La Maná, periodo 2012 - Caicedo Romero, Aracely Armenia (2014)
The objective of this research was to "evaluate the system of internal control of the process of procurement of public works at the Autonomous Government Decentralized Municipal Canton La Maná, period 2012," due to the control of securities presents shortcomings in compliance public works contract , same as they were delivered on the date stated in the contract document, by contractors, so he made the following specific objectives : a) Analyze the policies of internal control for the process of procurement of public works b) To review the activities of procurement process for public works c) Determine the adequacy and reliability of the financial information of the entity…….